2012
DOI: 10.1590/s1020-49892012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted by violence: children's well-being and families' economic, social, and cultural capital in Ciudad Juarez, Mexico

Abstract: Since 2008, Ciudad Juarez (Chihuahua, Mexico) has been undergoing a wave of violence due to a drug war, making the city a difficult environment in which to raise a family. This study uses qualitative methodology that incorporates 16 in-depth interviews with parents of children ages 0-5 years and 9 sets of photos from a subset of interviewed parents. The study explores how families' economic, social, and cultural capital has been disrupted by the violence and how it affects children's well-being. Social and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
0
20
0
4
Order By: Relevance
“…[20][21][22][23] Geissler et al (2014) found a positive association between homicide rates in Mexico and ambulatory care sensitive hospitalizations in border counties, a proxy for reduced access to care; no association was found between homicide rates and types of emergency department utilization in Arizona and California border counties. 23 A 50% decline in medical tourism by Americans to Mexico was estimated in 2010 due to fear and increased border wait times due to stricter security checks.…”
Section: New Contribution To the Literaturementioning
confidence: 99%
“…[20][21][22][23] Geissler et al (2014) found a positive association between homicide rates in Mexico and ambulatory care sensitive hospitalizations in border counties, a proxy for reduced access to care; no association was found between homicide rates and types of emergency department utilization in Arizona and California border counties. 23 A 50% decline in medical tourism by Americans to Mexico was estimated in 2010 due to fear and increased border wait times due to stricter security checks.…”
Section: New Contribution To the Literaturementioning
confidence: 99%
“…The insecurity has impacted not only social well-being and quality of life (Hernandez and Grineski 2012), but also economic activity and growth. The city has seen a dramatic drop in tourism (including foreigners seeking medical and dental care) and a significant rise in unemployment (to a rate that is twice that of Mexico).…”
Section: Study Contextmentioning
confidence: 99%
“…Este tipo de violencia se expresa a través de balaceras, desapariciones o control de los territorios mediante el miedo, lo cual implica el uso de tácticas como la exposición de cuerpos mutilados, el uso de mantas con mensajes a la ciudadanía o a otras agrupaciones, las explosiones de autos o establecimientos, entre otras. Las comunidades se ven afectadas al encontrar límites a los desplazamientos y riesgos en las actividades cotidianas, así como ante la fragmentación del tejido social (AguilarForero & Muñoz, 2015) y el favorecimiento de la pérdida de los capitales económico, social y cultural de las familias (Hernández & Grineski, 2012).…”
Section: Introductionunclassified